The Practice of Religious Tourism among Generation Z's Higher Education Students - Julio García-del Junco; Eva M. Sánchez-Teba; Mercedes Rodríguez-Fernández; Irene Gallardo-Sánchez (MDPI AG, 2021)
The purpose of this paper is to shed light on the possibilities offered by religious tourism according to Generation Z's education in values. Both the theoretical and empirical frameworks of the research have focused on Hofstede's Cultural Model, aiming to predict with a certain level of success the influence of cultural and social values on the consumption of religious tourism by the young age segment of Generation Z. A cross-cultural analysis was performed using exponential sampling (Snowball Sampling). All respondents were higher education students. The surveys were carried out using "Google Forms". The results obtained allow the design of a communication plan for the management of Religious Tourism according to the dimensions of Masculinity-Femininity, Individualism-Collectivism, Distance to Power, Risk Aversion, and Long-term Orientation.